Benchmarking river water quality in Malaysia - Zainudin, Zaki (Institution of Engineers Malaysia, 2010)
The water quality status of rivers in Malaysia has always been a cause for concern for various local authorities, government agencies as well as the public at large. Rivers in Malaysia are generally considered to be polluted with coherent examples such as Sg. Klang in Selangor (shown in Figure 1.1), Sg. Juru in Penang and Sg. Segget in Johor. From physical observation alone, one can deduce that something is not right with the current water quality condition of these rivers. From a scientific perspective though, it is still necessary to quantify the degree of pollution, in order to manage the pollution issues in a systematic and optimised fashion.